Muslim Minorities and Political Representation In the 2019 Bali Provincial Regional Representative Council Election - Ali Sodiqin; Nurdhin Baroroh (UIN Sunan Kalijaga Yogyakarta, 2025)
This study explored the success of the Balinese Muslim minority in winning the 2019 Regional Representative Council (DPD) election. The primary focus is to identify the factors that influenced this triumph and analyze the strategies employed and the roles played by the actors involved. This study uses a phenomenological approach complemented by Higley and Burton's elite theory. This theory explained the dynamics between actors through two distinct paths, namely